Intertextuality in Political Discourse: A Study of President Mohammadu Buhari’s 2015 Inaugural Speech - Magor Ellah, Stephen (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
This study examines the intertextual references in President Mohammadu Buhari’s 2015 presidential inaugural speech. The speech was purposively selected from the online version of The Guardian newspaper because it marked a change of government at the federal level from a ruling political party, People’s Democratic Party (PDP) to a hitherto opposition party: All Progressives’ Congress (APC). The data was then subjected to a discourse-pragmatic analysis using the theoretic concept of intertextuality. The findings reveal that the President dexterously intermixed political discourse with religious, literary, and historical discourses through manifest intertextuality and interdiscursivity. The study also indicates the President’s positivist, liberalist and religious ideological orientation. The study concludes that all texts are constellation of several other texts which are used to index the text producer’s ideology.